Global camera trap synthesis highlights the importance of protected areas in maintaining mammal diversity. Issue 2 (26th January 2022) - Chen, Cheng; Brodie, Jedediah F.; Kays, Roland; Davies, T. Jonathan; Liu, Runzhe; Fisher, Jason T.; Ahumada, Jorge; McShea, William; Sheil, Douglas; Agwanda, Bernard; Andrianarisoa, Mahandry H.; Appleton, Robyn D.; et al.
Abstract: The establishment of protected areas (PAs) is a central strategy for global biodiversity conservation. While the role of PAs in protecting habitat has been highlighted, their effectiveness at protecting mammal communities remains unclear. We analyzed a global dataset from over 8671 camera traps in 23 countries on four continents that detected 321 medium‐ to large‐bodied mammal species. We found a strong positive correlation between mammal taxonomic diversity and the proportion of a surveyed area covered by PAs at a global scale ( β = 0.39, 95% confidence interval [CI] = 0.19–0.60) and in Indomalaya ( β = 0.69, 95% CI = 0.19–1.2), as well as between functional diversity and PA coverage in the Nearctic ( β = 0.47, 95% CI = 0.09–0.85), after controlling for human disturbances and environmental variation. Functional diversity was only weakly (and insignificantly) correlated with PA coverage at the global scale ( β = 0.22, 95% CI = −0.02–0.46), pointing to a need to better understand the functional response of mammal communities to protection. Our study provides important evidence of the global effectiveness of PAs in conserving terrestrial mammals and emphasizes the critical role of area‐based conservation in a post‐2020 biodiversity framework.